2021
DOI: 10.34172/aim.2021.60
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of COVID-19; Acute Auto-inflammatory Disease (Endotheliopathica & Leukocytoclastica COVIDicus)

Abstract: Background: The pathogenesis of the COVID19 pandemic, that has killed one million nine hundred people and infected more the 90 million until end of 2020, has been studied by many researchers. Here, we try to explain its biological behavior based on our recent autopsy information and review of literature. Methods: In this study, patients with a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) result were considered eligible for enrollment. Histopathological examinations were done on 13 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Postmortem examinations showed that the main focus of viral damages is the endothelial cells (44)(45)(46). We have observed endothelial damages in our autopsy cases in the endothelial cells (endotheliopathica), hepatocytes, neutrophils, and mitochondria (Figures 1-5) of involved organs (27). Therapies preventing vascular damages and medications that improve endothelial dysfunction, such as the inhibitors of angiotensin-converting enzyme, angiotensin receptor blockers, and statins may improve the outcome in COVID-19 (42).…”
Section: Covid-19 and Endothelial Nucleolar Stressmentioning
confidence: 57%
See 1 more Smart Citation
“…Postmortem examinations showed that the main focus of viral damages is the endothelial cells (44)(45)(46). We have observed endothelial damages in our autopsy cases in the endothelial cells (endotheliopathica), hepatocytes, neutrophils, and mitochondria (Figures 1-5) of involved organs (27). Therapies preventing vascular damages and medications that improve endothelial dysfunction, such as the inhibitors of angiotensin-converting enzyme, angiotensin receptor blockers, and statins may improve the outcome in COVID-19 (42).…”
Section: Covid-19 and Endothelial Nucleolar Stressmentioning
confidence: 57%
“…The interaction of viral N-protein with nucleolin is a possible description of how the localization of coronavirus N-protein takes place in the nucleolus. This protein localizes to the nucleolus and is involved in the regulation of cell growth and cell cycle (27,28). Accordingly, this finding provides fundamental insights into how and why the nucleolus is targeted by coronaviruses resulting in disrupted normal action and the production of nucleolar proteins to facilitate virus replication.…”
Section: Human Nucleolus and Viral Infectionsmentioning
confidence: 96%
“…This increase in vascular layer thickness may result from hypoxia and inflammation or a reaction to intense endothelial injury that causes dysfunction in the underlying vascular wall. These findings highlight the importance of further research into the mechanisms behind these changes and how they may contribute to the development of new treatments for COVID-19 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue damage can cause interstitial acute inflammatory cell reaction with degenerative reaction and necrosis. Endothelial cell degeneration at the vessel wall was confirmed by CD34 and factor VIII immunohistochemistry staining ( 14 ).…”
Section: Discussionmentioning
confidence: 99%